Evaluation of Wound Healing Activity of Three Different Species of Bauhinia on Experimental Animal Models - Goutam Ghosh (Journal of Global Pharma Technology, 2018)
Objective: .Bauhinia racemosa, Bauhinia tomentosa and Bauhinia vahlii are the most important indigenous plants of Odisha. Traditionally, these plants are used in wound healing, skin abrasions, pimples, blister and boils. To validate the folkloric claims of these plants, methanolic extracts of these plants were evaluated by incision and excision wound models. Methods: The experimental animals were divided into five groups of six for each model. The animals in test group were treated with the test extracts of these three plants topically in the form of ointment and reference standard, Povidone Iodine was applied on the incised wound of animals of standard group. Healing measured by the rate of wound contraction, complete epithelialization, and granulation of tissue. On day 14, BV, BR and BT were recorded as 250, 210 and 125 g/cm2 respectively as compared to the control, whereas, Povidone iodine showed the tensile strength of 230g/cm2. Results: Preliminary phytochemical screening of the extract revealed the presence of phenolics, flavonoids, saponins and tannins. The rapid wound contraction and decreased rate of epithelialization time suggest that these plant extracts extract may have better wound healing potentials.